A call to strengthen the global strategy against schistosomiasis and soil-transmitted helminthiasis: the time is now. Issue 2 (February 2017) - Lo, Nathan C; Addiss, David G; Hotez, Peter J; King, Charles H; Stothard, J Russell; Evans, Darin S; Colley, Daniel G; Lin, William; Coulibaly, Jean T; Bustinduy, Amaya L; Raso, Giovanna; Bendavid, Eran; et al.
Summary: In 2001, the World Health Assembly (WHA) passed the landmark WHA 54.19 resolution for global scale-up of mass administration of anthelmintic drugs for morbidity control of schistosomiasis and soil-transmitted helminthiasis, which affect more than 1·5 billion of the world's poorest people. Since then, more than a decade of research and experience has yielded crucial knowledge on the control and elimination of these helminthiases. However, the global strategy has remained largely unchanged since the original 2001 WHA resolution and associated WHO guidelines on preventive chemotherapy. In this Personal View, we highlight recent advances that, taken together, support a call to revise the global strategy and guidelines for preventive chemotherapy and complementary interventions against schistosomiasis and soil-transmitted helminthiasis. These advances include the development of guidance that is specific to goals of morbidity control and elimination of transmission. We quantify the result of forgoing this opportunity by computing the yearly disease burden, mortality, and lost economic productivity associated with maintaining the status quo. Without change, we estimate that the population of sub-Saharan Africa will probably lose 2·3 million disability-adjusted life-years and US3·5 billion of economic productivity every year, which is comparable to recent acute epidemics, including the 2014 Ebola and 2015 Zika epidemics. We propose that the time is now to strengthen the global strategy to address the substantial disease burden of schistosomiasis and soil-transmitted helminthiasis.